(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study explores the development of the nonprofit sector in the Kingdom of Saudi Arabia during the period 2022–2024 and evaluates the impact of Saudi Vision 2030 on its performance. Drawing on official reports, the analysis revealed significant growth across all sub-sectors, including endowments, social organizations, voluntary initiatives, and cooperative activities. The sector’s contribution to GDP increased to 3.3% of the 5% target set within Vision 2030. Human capital also expanded considerably, with the proportion of employees rising from 45% to 64% of the total workforce, alongside a substantial increase in training program beneficiaries from 284 in 2022 to 725 in 2024. Furthermore, local and international partnerships expanded, peaking at 31 in 2023 before stabilizing at 23 in 2024. Collectively, these indicators reflect accelerated and balanced growth of the nonprofit sector, driven by supportive legislative and regulatory frameworks. Nonetheless, the analysis highlighted persistent gaps in the availability of sectoral and regional data. Despite gradual improvements, detailed and disaggregated information remains limited, a challenge most evident in the 2022 reports. The significance of this study lies in providing a comprehensive analytical perspective that connects the sector’s quantitative indicators with sustainability requirements, thereby offering valuable insights for policymakers and researchers in formulating more effective strategies to strengthen its role in economic and social development. Looking ahead, the research outlines future opportunities, including the advancement of sustainable financing models (endowments, social investment, and digital donations), the promotion of digital innovation and open data to foster transparency, and the development of advanced governance frameworks aligned with the objectives of Saudi Vision 2030.